Fuel for life: Domestic cooking fuels and women's health in rural China? - Peng Nie; Alfonso Sousa-Poza; Jianhong Xue (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2016)
Using longitudinal and biomarker data from the China Family Panel Studies and the China Health and Nutrition Survey, this study examines the association between the type of domestic cooking fuel and the health of women aged Ï16 in rural China. Regarding three major domestic cooking fuels (wood/straw, coal and liquefied natural gas (LNG)), we find that, compared to women whose households cook with dirty fuels like wood/straw, women whose households cook with cleaner fuels like LNG have a significantly lower probability of chronic or acute diseases and are more likely to report better health. Even after controlling for unobserved individual heterogeneity, we find some evidence that women in households cooking with LNG are less likely to suffer from chronic/acute diseases. Cooking with domestic coal instead of wood or straw is also associated with elevated levels of having certain risks (such as systolic and diastolic blood pressure) related to cardiovascular diseases.
urn:nbn:de:bsz:100-opus-12356
Keywords: I10; D10; J10; Q53; 330; household cooking fuels; health; women; rural China